Crystallographic studies of fish hemoglobins - Delatorre, Plínio; Delamano, Márcia; Fadel, Valmir; Honda, Rubens Tomio; Smarra, André Luís Soares; Canduri, Fernanda; Oliveri, Johnny Rizzieri; Bonilla-Rodriguez, Gustavo Orlando; de Azevedo Júnior, Walter Filgueira (Eclética Química, 2000)
The present work reports our succesfull experience concerning crystallization of four fish hemoglobins from three Brazilian species of Teleosts: Liposarcus anisitsi, Brycon cephalus and Piaractus mesopotamicus. The data shown here is part of a systematic functional and structural study of fish hemoglobins with the aim of better understanding the outstanding range of functional and structural properties exhibited by these proteins. We also present a reduced sparse-matrix method for crystallization of fish hemoglobins, which can reduce the amount of hemoglobin initially used in the crystallization experiments.